2012
DOI: 10.1111/fcp.12009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cysteamine bitartrate following intraduodenal delivery

Abstract: Cysteamine is approved for the treatment of cystinosis and is being evaluated for Huntington's disease and non-alcoholic fatty liver disease. Little is known about the bioavailability and biodistribution of the drug. The aim was to determine plasma, cerebrospinal fluid (CSF), and tissue (liver, kidney, muscle) cysteamine levels following intraduodenal delivery of the drug in rats pretreated and naïve to cysteamine and to estimate the hepatic first-pass effect on cysteamine. Healthy male rats (n = 66) underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Similar levels of cysteamine in the kidney were achieved following intraduodenal administration in rats. Likewise, plasma levels were similar to those observed in mice injected intraperitoneally 15 . This suggests that the cysteamine dose used in this study is subtherapeutic for the testes which is likely to be the case in cystinosis patients, which could, in turn, explain the lack of effect of cysteamine on the development of gonadal failure.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar levels of cysteamine in the kidney were achieved following intraduodenal administration in rats. Likewise, plasma levels were similar to those observed in mice injected intraperitoneally 15 . This suggests that the cysteamine dose used in this study is subtherapeutic for the testes which is likely to be the case in cystinosis patients, which could, in turn, explain the lack of effect of cysteamine on the development of gonadal failure.…”
Section: Discussionsupporting
confidence: 81%
“…Tissue cystine levels were evaluated in the Laboratory of Metabolic Biochemistry Unit, Department of Pediatric Medicine, Bambino Gesù Children's Hospital, Rome, Italy, with modifications from the method that was published earlier 13,14 . In addition, plasma and tissue cysteamine levels were evaluated in the UCSD Biochemical Genetics and Metabolomics Laboratory, University of California San Diego, as was published earlier 15 …”
Section: Methodsmentioning
confidence: 99%
“…However, ensuring an adequate supply of precursor amino acids, especially cysteine, to support intracellular glutathione synthesis is a proven strategy for preventing glutathione depletion in the liver 12, 13 . Cysteamine is a small molecule (HS-CH 2 -CH 2 -NH 2 ) which is able to cross cell membranes easily and reacts with extracellular cystine to form cysteine which is then readily taken up into cells and used to support glutathione synthesis 1416 . In an open-label pilot study, 6 months of treatment with cysteamine bitartrate improved serum alanine (ALT) and aspartate aminotransferase (AST) levels and increased adiponectin in children with NAFLD 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, a recent study in rats has shown that cysteamine absorption is greater in naïve than in animals pre-treated with cysteamine (ref. 25 to follow). Better absorption in the Naïve group may be explained by a recent animal study which reports that cysteamine uptake from the intestinal tract is a saturable carrier-mediated process that involves organic cationic transporters.…”
Section: Discussionmentioning
confidence: 97%
“…Firstly, cysteamine absorption is greater when drug is taken during fasting than with high fat diet. Secondly, a recent study in rats has shown that cysteamine absorption is greater in naïve than in animals pre‐treated with cysteamine (ref . to follow).…”
Section: Discussionmentioning
confidence: 99%